Aktivitas Gastroprotektif Kombinasi Ekstrak Kulit Batang Mimba (Azadirachta indica A. Juss) dan Rimpang Kunyit (Curcuma domestica Linn.) pada Tikus Putih yang Diinduksi Asetosal - SANTI PUMA SARI; ABDUL MUN’IM; DINI KUSUMANINGTYAS (Fakultas Farmasi Universitas Pancasila, 2013)
Some pre-clinical and clinical studies reported that neem (Azadirachta indica A. Juss) bark and turmeric (Curcuma domestica Linn.) rhizome extracts demonstrated strong gastroprotective activities. In this studies, the effect of combination of neem bark and turmeric rhizome extracts were investigated on acetosal-induced gastric ulcer in rats.The combination is expected to produce synergic effect on the gastric ulcer. The combination of extracts was administered orally in various doses for 7 days prior to the ulcer induction. On the 8th-day rats were given asetosal 400 mg/kg bw to induce gastric ulcer. All rats were sacrificed 8 hours after asetosal induction for the determination of ulcer index, total acidity, mucus thickness and histophatological examination. The combination of neem bark extract (250 mg/kg bw) and turmeric rhizome extract (50 mg/kg bw) was significantly reduced the ulcer index (a = 0.05). This result was substantiated by histophatological examinations. Results of this study showed that combination of neem bark and turmeric rhizome extracts have synergic gastroprotective activities.